Pengaruh Pemilihan Lokasi Terhadap Keberhasilan Usaha UMKM Makanan di Sekitar Jalan HS. Roggo Waluyo Karawang Barat - Alya Rizky Sauzan; Nelly Martini (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the influence of business environment conditions, business accessibility with infrastructure, and business location costs on the success of food MSMEs on Jalan HS. Ronggo Waluyo, West Karawang. The objects of this study are food MSMEs around Jalan HS. Ronggo Waluyo, Karawang, which is number 30 food MSME entrepreneurs. A saturated sampling technique was applied in this study, so that the sample size and population size were the same, namely 30 food MSME entrepreneurs. Data collection used the census method, and the data were processed and tested using multiple regression analysis with SPSS 26 software. The study proved that business environment conditions, accessibility with infrastructure, and location costs have a positif and significant effect on the success of MSME businesses. To achieve business success, the variation of the three variabels was proven by an Adjusted R2 value of 95%. The factor that dominates the influence of business success is location cost.